Parliamentarizing a Politicized Policy: Understanding the Involvement of the European Parliament in UN Climate Negotiations - Delreux, Tom (2019)
Climate change is a central topic of concern for EU international diplomacy and is the site of increased politicization globally. Concomitantly, a parallel process of parliamentarization of the EU has unfolded. Whilst the European Parliament (EP) has enjoyed significant powers in internal policy-making on climate change, since the entry into force of the Lisbon Treaty in 2009 the EP has gained the right to veto the EU’s ratification of international (climate change) agreements. This development raises questions about our understanding of the EP as an actor in international climate diplomacy that this article addresses through the following research question: What impact have the increased powers of the EP had on its involvement in UN climate diplomacy? We analyze the EP’s evolving role in international climate diplomacy through an evaluation of its policy preferences prior to international climate conferences (COPs) and its activities during those meetings. We find evidence that the EP’s preferences have become more moderate over time, and that it is also more active at COPs and increasingly engaged with a range of more important actors. However, we find little evidence that the EP’s involvement in international negotiations is significantly different when it holds a veto power, which we attribute to a willingness to depoliticize internal EU climate negotiations to secure policy gains at the international level.